Community-based elderly data management system: enhancing data recording and reporting by local stakeholders - Rosha, Putri Tiara; Oksidriyani, Safrina; Ni`ma, Neli Syahidah; Ghassanie, Firly Azra; Himmah, Irna Mufidatul; Artanti, Emilia Indri; Setiawan, Aulia Putri; Ainun, Khotami Nurfa; Setyowati, Florensia Indah (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Senior Integrated Health Care Post (POKSILA) is an elderly health monitoring activity at the community level. Kedungmundu Public Health Center has the largest number of elderly people and POKSILA in Semarang. Participant measurements are recorded manually through cadre notebooks and POKSILA forms owned by participants. Also, reporting is still limited, and the format is not uniform. This POKSILA data can be used to monitor the health condition of the elderly continuously.Methods: To solve the problem, the stages of service activities include an overview of the characteristics of the elderly, need assessment, activity preparation, and handing over monitoring books to community health centers.Results: Most participants in POKSILA were female (88%) and aged 60-74 (52%). Based on FGD, develop a recording book for cadres and a monitoring book for elderly participants. The book will be developed on cadre needs, Mentari Sehat Nusantara apps, and guidelines for elderly health. To develop the book, we consulted and brainstormed with the experts in Kedungmundu PHC about the design and content of the book. Within local data and cross-collaboration, the tools should be appropriate to local conditions and easily understood by the communities. This community-based service initiative has demonstrated the potential for improving health monitoring and service delivery for elderly populations in Kedungmundu, Semarang.Conclusion: By addressing key challenges identified in the FGDs and implementing standardized tools for health data recording, the initiative has made important strides toward enhancing the quality of elderly care in the region.